2021
DOI: 10.1371/journal.pone.0257384
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated radiotherapy for newly diagnosed elderly glioblastoma patients: A systematic review and network meta-analysis

Abstract: Objective To evaluate different hypofractionated radiotherapy (HRT) regimens for newly diagnosed elderly glioblastoma (GBM) patients. Methods We performed a systematic review with network meta-analysis (NMA), including searches on CENTRAL, Medline, EMBASE, CINAHL, clinical trial databases and manual search. Only randomized clinical trials (RCTs) were included. Primary outcomes: overall survival (OS) and adverse events (AE). Secondary outcomes: progression-free-survival (PFS) and quality of life (QoL). We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…A systematic review and network meta-analysis (NMA) also showed that OS estimates from NMA did not provide strong evidence of a difference between different hypofractionated radiotherapies of 40 Gy versus 45 Gy; 34 Gy versus 45 Gy; 25 Gy versus 45 Gy; 34 Gy versus 40 Gy and 25 Gy versus 34 Gy ( 99 ). A multi-institutional retrospective study in Korea reported that conventional radiotherapy significantly improved OS compared with short-course radiotherapy in selected elderly patients amenable to chemoradiation ( 100 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A systematic review and network meta-analysis (NMA) also showed that OS estimates from NMA did not provide strong evidence of a difference between different hypofractionated radiotherapies of 40 Gy versus 45 Gy; 34 Gy versus 45 Gy; 25 Gy versus 45 Gy; 34 Gy versus 40 Gy and 25 Gy versus 34 Gy ( 99 ). A multi-institutional retrospective study in Korea reported that conventional radiotherapy significantly improved OS compared with short-course radiotherapy in selected elderly patients amenable to chemoradiation ( 100 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Дискусія щодо місця гіпофракціонування в променевому лікуванні нейроонкологічних пацієнтів триває. Про це свідчать недавно опубліковані системні огляди та метааналізи [10][11][12][13][14][15].…”
Section: аналіз співвідношення ризику смерті та прогресування залежно...unclassified